INDIAN POSITION ON LEGAL STATUS OF REFUGEES - Shalini, Kunjana; Garg, Seema (Nimitmai Review Journal, 2020)
India is one of the few countries in the world which has experienced refugee situation, time and again and that too on a gigantic scale in the last less than half-a-century. History of India is marked by large scale migrations of people from other countries and continents. These migrations had principally taken place across of two gateways- Hindukush Mountains in the west and patkoi range in the East. As Prof. M.P. Singh observed(M.Katju,”India’s Perception of Refugee Law” 251-253, ISIL year book of International Humanitarian and RefugeeLaw,2001.):” From the times immemorial, people from different parts of the world have been coming to India in various categories such as travellers, invaders, settlers, refugees etc., and have made, this land their home with or without separate identity”. An intricate legal question arose as to the legal status of displaced persons as the definition of displaced person provided by the Rehabilitation Finance Administration Act of 1948, is at variance from the definition of the term refugee provided by the 1951 convention relating to the status of refugees. In this case, the situation creating the refugees was the result of an agreement between the two governments. Prof. Khan aptly observed that the plight of the people who had migrated was the same as that of refugees. They were displaced from one country to another, had undergone harrowing experiences and had sought refuge in a country not of their origin.( J.N. sexana”Legal Status of Refugees: Indian Psition”501-515, Indian journal of International law1986.)